2007
DOI: 10.1111/j.1467-985x.2007.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

A Graphical Chain Model for Reciprocal Relationships Between Women’s Gender Role Attitudes and Labour Force Participation

Abstract: We use a graphical chain model to investigate the reciprocal relationships between changes in women's labour force participation following entry into parenthood and changes in gender role attitude. Results suggest that attitudes are not fixed and that revision of these attitudes in the light of recent life course events is an important process. The adaptation of attitudes to events appears to be stronger than the selection of individuals on the basis of attitudes. We show that it is not entry into parenthood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 22 publications
4
55
0
5
Order By: Relevance
“…In line with previous studies (Berrington et al, 2008;Himmelweit and Sigala, 2004), evidence is found of a reciprocal relationship between women's gender role attitudes and labour market participation, suggesting that behaviour and attitudes reinforce each other. Women with less traditional attitudes before having children decrease their labour market hours less.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies (Berrington et al, 2008;Himmelweit and Sigala, 2004), evidence is found of a reciprocal relationship between women's gender role attitudes and labour market participation, suggesting that behaviour and attitudes reinforce each other. Women with less traditional attitudes before having children decrease their labour market hours less.…”
Section: Discussionsupporting
confidence: 90%
“…They find increases in educational attainment and full-time employment result in more egalitarian Work,employment and society 26(3) attitudes, while marriage, parenthood and reductions in paid work are associated with more traditional attitudes (Cunningham et al, 2005;Fan and Marini, 2000;Himmelweit and Sigala, 2004;Kan, 2007). Berrington et al (2008) suggest that it is not entry into parenthood as such, but the change in women's economic activity as a consequence of parenthood which is associated with attitude change. Himmelweit and Sigala (2004) show that changes in attitudes or behaviour are more likely when mothers' labour market status is inconsistent with their attitudes towards women's employment.…”
Section: Introductionmentioning
confidence: 99%
“…Women with modern 'egalitarian' attitudes are generally found to work more (hours) than women with traditional attitudes (Bolzendahl and Myers, 2004;Van Wel and Knijn, 2006). The same holds true for the working-mother role model during childhood (Berrington et al, 2008;Myers and Booth, 2002). The most obvious differences in social norms and attitudes exist between working and non-working women.…”
Section: Theoretical Frameworkmentioning
confidence: 77%
“…In fact, recent research points to the dual causality between preferences and outcome, Himmelweit and Sagwala (2005) find preferences to change to reflect outcome. While Berrington et al (2008), using graphical chain models, establish women to be more likely to change their attitudes than pursue market outcomes on the basis of their attitudes.…”
Section: The Penalty To Motherhood Previous Findingsmentioning
confidence: 99%